Prevalence Of Anemia Among Adolescent Girls in An Urban Slum - Meenal Vinay Kulkarni; P M Durge; N B Kasturwar (Medsci Publications, 2012)
Introduction: Nutritional anemia is one of India's major public health problems. Adolescence is a vulnerable period in the human life cycle for the development of nutritional anemia. Anemia in adolescent girls contributes to maternal and foetal mortality and morbidity in future. Most of the health care services in India are for mother and child group. Objectives: To estimate prevalence of anemia among adolescent girls in an urban slum and to study socio-demographic and menstrual factors associated with it. Material and methods: A cross sectional community based study was conducted among 272 adolescent girls in an urban slum area under Urban Health Training centre, department of Community Medicine, NKP Salve Institute of Medical science, Nagpur from June 2009 to February 2010. Out of five areas one area was selected by simple random sampling. Information regarding socio-demographic and menstrual factors was recorded in pre-designed, pre -tested proforma. Hemoglobin estimation was done by Sahli's haemoglobinometer. Data was analyzed by mean, standard deviation and chi square test. Results: Prevalence of anemia was found to be very high (90.1%) among adolescent girls. Majority of the girls were having mild or moderate anemia (88.6%). A significant association was found between adolescent girl's education, mother's occupation and anemia. No association was found between menstrual factors and anemia. Conclusions-Nutrition education along with nutritional supplementation and iron folic acid tablets should be provided to all girls.